2017
DOI: 10.1093/jb/mvx032
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ser/Thr phosphatase PPM1D induces neutrophil differentiation in HL-60 cells

Abstract: Protein phosphatase Magnesium-dependent 1, Delta (PPM1D) is a wild-type p53-inducible Ser/Thr phosphatase that acts as a negative regulator of the p53 tumor suppressor. Gene amplification and overexpression of PPM1D have been reported in various cancers including leukemia and neuroblastoma. Therefore, PPM1D is a promising target in cancer therapy. It has been reported that PPM1D knockout mice exhibit neutrophilia in blood and show a defective immune response. Here, we found that inhibition of PPM1D induced neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Additionally, existing evidences suggests that PPM1D induces transformation virus‐infected T cells into leukemic cells, which contributes to the development of ATLL . And in another type of leukemia, APL, PPM1D inhibition is observed to induce neutrophil differentiation in human APL cell line HL‐60, suggesting that targeting PPM1D inhibits the APL progression . Although the previous studies indicate that PPM1D play an important role in some solid tumors as well as hematologic malignancies, the role of PPM1D in AML has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, existing evidences suggests that PPM1D induces transformation virus‐infected T cells into leukemic cells, which contributes to the development of ATLL . And in another type of leukemia, APL, PPM1D inhibition is observed to induce neutrophil differentiation in human APL cell line HL‐60, suggesting that targeting PPM1D inhibits the APL progression . Although the previous studies indicate that PPM1D play an important role in some solid tumors as well as hematologic malignancies, the role of PPM1D in AML has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hematologic malignancies, there is evidence that PPM1D expression is inhibited by a potent cancer chemotherapeutic agent for acute promyelocytic leukemia (APL), which activates p38 MARK/p53 signaling and promotes APL cell apoptosis . Additionally, PPM1D is reported to contribute to tumorigenesis through inducing the transformation of leukemic cells in adult T‐cell leukemia/lymphoma (ATLL), and the inhibition of PPM1D is revealed to mediate neutrophil differentiation in human APL, implying that PPM1D is also involved in the initiation and development of hematologic malignancies . As for in AML, PPM1D mutant strongly outcompetes the wild‐type PPM1D and correlates with increased drug resistance in the treatment .…”
Section: Introductionmentioning
confidence: 99%
“… 10 As for hematological malignancies, PPM1D inhibition facilitates cell differentiation as well as induces G1 arrest in acute promyelocytic leukemia cells. 11 In addition, ectopic expression of PPM1D suppresses DNA damage induced Chk and p38 MAPK phosphorylation in acute promyelocytic leukemia. 12 Whereas for AML, it still lacks information about the function of PPMID in disease development and progression.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 As for hematological malignancies, suppression of PPM1D induces neutrophil differentiation and G1 arrest in human promyelocytic leukemia cells, and inhibition of PPM1D enhances the arsenic trioxide-induced activation of Chk2/p53 and p38 MAPK/p53 signaling pathway. 11 , 12 In addition, mouse model of adult T-cell leukemia/lymphoma discloses that Tax + PPM1D −/− mice present with less tumorigenesis compared with Tax + PPM1D +/+ mice. 13 …”
Section: Introductionmentioning
confidence: 99%
“…PPM1D (Protein phosphatase magnesium-dependent 1δ, also known as Wip1, PP2Cδ), a p53-inducible Ser/Thr phosphatase, is involved in cellular homeostasis via negative feedback of the p53-pathway[9]. PPM1D also has multiple functions in cellular differentiation and immune responses[10, 11]. Recently, it has been reported that PPM1D has a critical role in metabolism.…”
Section: Introductionmentioning
confidence: 99%